Different names, different discrimination? How perceptions of names can explain rental discrimination - Martiniello, Billie; Verhaeghe, Pieter-Paul (Frontiers in Sociology, 2023)
The aim of this research is to look into how signals carried by names can contribute to the explanation of why rental discrimination is measured. Ethnic discrimination on the rental housing market is a widespread phenomenon that is increasingly captured in an objective way by means of correspondence studies. This methodology assumes that the trigger for the measured discriminatory behavior is the signal of ethnic origin in names. Nonetheless, previous research found that names also contain other signals such as religiosity, social class and educational level. The current study relates data of 3.753 correspondence tests on the Flemish rental housing market in Belgium to survey data about the perception of the used names in the correspondence tests in terms of ethnic origin, gender, religiosity, social class and educational level. By doing so, we can set a step in the direction of why discrimination is measured. We find that realtors discriminate based on the perception of a name as religious, which we describe as religious taste-based discrimination. Besides, we also find indications for statistical discrimination. For landlords, the perception of a name as non-European increases discrimination, indicating ethnic taste-based discrimination.